Immersive virtual reality training in radiology: impact on motivation, interest, engagement, and learning outcomes - Fröhlich, Laureen; Görlach, Jannis; Thormählen, Thorsten; Mahnken, Andreas H. (Frontiers in Education, 2025)
BackgroundImmersive virtual reality (IVR) is becoming increasingly important in medical education. In radiology, IVR as a tool for practicing image interpretation and diagnosis of pathologies has rarely been subject of research to date. This exploratory study investigated a self-programmed IVR application and its potential to improve radiology education for medical students.MethodsAn IVR learning environment was programmed which enables users to view 3D models of real patients and interact with them using various tools. Fourth- to sixth-year medical students (n = 26) participated in a 1 h IVR training session in small groups between November 2022 and January 2023. Subsequently, they completed an anonymous online survey comprising 37 items. Data were analyzed, with correlations examined using Spearman’s non-parametric rank correlation.ResultsThe IVR training increased students’ motivation (M = 3.6) and interest in radiology (M = 3.2) and fostered enjoyment (M = 3.7) as well as a more active (M = 3.6) and intensive (M = 3.3) engagement. IVR was considered a helpful tool to enhance the practical relevance of radiology education, to improve the immediate cognitive and psychomotor learning outcomes related to anatomy and radiology, such as interpreting cross-sectional images (M = 3.5) and identifying anatomical structures (M = 3.6) as well as pathological changes (M = 3.3) and to promote skill development (M = 3.2), learning transfer (M = 3.2) and long-term knowledge retention (M = 3.3). The usability, design, tools and didactic functions of the IVR application are strongly associated with learning process- and learning outcome-related variables.ConclusionIVR-based learning is a promising addition to traditional radiology education to enhance motivation, interest and learning. However, the success of IVR depends on its design, usability and integration into the curriculum. The study highlights the need for further research on the added value of IVR across the educational sector.